2018
DOI: 10.1111/ijfs.13837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milling method on the chemical composition and antioxidant capacity of Tartary buckwheat flour

Abstract: Summary Tartary buckwheat has attracted increasing attention as a potentially functional food source because of its bioactive components and health benefits. However, little information is available concerning the effect of different milling methods (ultrafine milling (UM), roller milling (RM), stone milling (SM) and wet milling (WM)) on the chemical composition and antioxidant capacity of Tartary buckwheat flour. UM had an important role in reducing the average particle size and in brightening the colour of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…The phenolic compounds present in the plant‐based foods have been proposed as food supplements for the management of type 2 diabetes mellitus due to their promising antioxidant and hypoglycemic effect reported in various in vitro, in vivo researches and clincial trials (Lin et al, ). The recent increasing trend of research to produce novel plant food products rich in phenolic compounds, such as Tartary buckwheat flour (Liu, He, Wang, & Wang, ), lettuce waste flour (Plazzotta, Sillani, & Manzocco, ), pomegranate peel extract chewing gum (Palabiyik et al, ), jambolan (Singh, Singh, Kaur, & Singh, ), and apple pomace (Wang, Boussetta, Lebovka, & Vorobiev, ) may suggest the role of plant‐based foods in human health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenolic compounds present in the plant‐based foods have been proposed as food supplements for the management of type 2 diabetes mellitus due to their promising antioxidant and hypoglycemic effect reported in various in vitro, in vivo researches and clincial trials (Lin et al, ). The recent increasing trend of research to produce novel plant food products rich in phenolic compounds, such as Tartary buckwheat flour (Liu, He, Wang, & Wang, ), lettuce waste flour (Plazzotta, Sillani, & Manzocco, ), pomegranate peel extract chewing gum (Palabiyik et al, ), jambolan (Singh, Singh, Kaur, & Singh, ), and apple pomace (Wang, Boussetta, Lebovka, & Vorobiev, ) may suggest the role of plant‐based foods in human health.…”
Section: Introductionmentioning
confidence: 99%
“…The recent increasing trend of research to produce novel plant food products rich in phenolic compounds, such as Tartary buckwheat flour (Liu, He, Wang, & Wang, 2018), lettuce waste flour (Plazzotta, Sillani, & Manzocco, 2018), pomegranate peel extract chewing gum (Palabiyik et al, 2018), jambolan (Singh, Singh, Kaur, & Singh, 2018), and apple pomace (Wang, Boussetta, Lebovka, & Vorobiev, 2018) may suggest the role of plant-based foods in human health.…”
Section: Introductionmentioning
confidence: 99%
“…Milling techniques used in the food industry employ mechanical force to break the grains into smaller fragments or fine particles. [15]. Previous studies reported the use of roller milling process in dehulled whole buckwheat to obtain a flour and the separation of this flour into various fractions from outer to inner parts [2,16].…”
mentioning
confidence: 99%
“…TA B L E 3 Dough farinograph property of flour mixture bound phenolics into free forms (Kim et al, 2013), therefore conducing to higher extractability of phenolics (including flavonoids) after thermal extrusion. 403.5~895.9 mg/100 g in dry-milled tartary buckwheat flour (Liu et al, 2018). In this study, noodles making process evoked a 20~80…”
Section: Tpc and Flavonoids In Cooked Noodlesmentioning
confidence: 52%